Demands and resources of a long-standing bring-your-dog-to-work program: a constant comparative analysis - Braxton Schieler; Niwako Ogata; Leanne O. Nieforth (Frontiers in Public Health)
IntroductionGiven the evidence that companion animals may provide social and emotional support to their human counterparts, some companies have begun offering bring-your-dog-to-work programs in an effort to reduce employee strain and improve workplace wellness outcomes. The purpose of this qualitative study was to investigate how a long-standing bring-your-dog-to-work program at a large midwestern university veterinary college, the Dogs at Work Program, impacted the workplace well-being of program participants.MethodsA total of n = 11 staff and faculty members who participated in the program completed semi-structured interviews about their experiences. Interviews were analyzed using the constant comparative technique.ResultsConstant comparative analysis revealed four themes situated within a job demands-resources theoretical framework: (1) Dogs providing emotional support as a resource, (2) Dogs providing social support as a resource, (3) Increased responsibility as a demand, and (4) Lack of adherence to program rules as a demand. Results indicated that bringing pet dogs into the workplace was viewed positively because the dogs provided an impetus for pleasant breaks from stressful work, improved work-life balance, and helped to develop and enhance social relationships. On the other hand, participants also mentioned that dogs could be a distraction from workplace productivity, especially if they were poorly behaved.DiscussionWell-enforced policies for dog activity and behavior are critical to ensure that dogs at work do not diminish productivity or upset some employees. Nevertheless, bring-your-dog-to-work-programs appear to show promise in terms of reducing strain and may be linked to improved mental health outcomes.